Clinical manifestations of cytomegalovirus-associated posterior uveitis and panuveitis in patients without human immunodeficiency virus infection - Pathanapitoon K. (2014)
Importance: Little attention has been paid to clinical features of cytomegalovirus (CMV) infections in individuals without human immunodeficiency virus (HIV). Objective: To describe the clinical manifestations and comorbidities of patients without HIV infection who have CMV-associated posterior uveitis or panuveitis. Design and Setting: Retrospective observational case series in an academic research setting. Participants: The medical records were reviewed of 18 patients (22 affected eyes) diagnosed as having posterior uveitis or panuveitis who had aqueous positive for CMV by polymerase chain reaction techniques. Main Outcome Measures: Demographic data, clinical manifestations, and associated systemic diseases were recorded. Results: Ocular features included focal hemorrhagic retinitis (n=13) and peripheral retinal necrosis (n=7). Two eyes had no focal retinal lesions but manifested vasculitis and vitritis. All patients exhibited vitreous inflammation. Inflammatory reactions in anterior segments developed in 14 of 22 eyes (64%). Retinal vasculitis was observed in 16 of 22 eyes (73%) and included mostly arteries (in 13 of 16 eyes [81%]). Eleven of 18 patients were taking immunosuppressive medications (5 for hematologic malignant diseases, 4 for systemic autoimmune diseases, and 2 following organ transplants). One additional patient was diagnosed as having non-Hodgkin lymphoma 3 months after the onset of CMV-associated panuveitis, and another patient had primary immunodeficiency disorder. Of the remaining 5 patients, 2 had diabetes mellitus, and 3 had no associated systemic diseases and exhibited no evidence of immune deficiency. Conclusions and Relevance: Cytomegalovirusassociated infections of posterior eye segments can develop in patients without HIV infection who have compromised immune function of variable severity but may occur also in individuals who have no evidence of immune insufficiency. Cytomegalovirus infections located in posterior eye segments in patients without HIV infection caused intraocular inflammatory reaction in all cases and demonstrated more variable clinical presentation than classic CMV retinitis observed in patients with HIV infection. © 2013 American Medical Association. All rights reserved.